ANALISIS KESENJANGAN ANTARA POTENSI, ANGGARAN DAN REALISASI PENDAPATAN RETRIBUSI IZIN GANGGUAN (Studi Kasus pada Kabupaten Indragiri Hulu - Riau) - , Rika Gustini; , Irwan Taufiq Ritonga, S.E., M.Bus. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The data concerning the local revenue realization of Indragiri Hulu District and the 2009 regulation on disturbance permit levy of each sub-district has showed a gap among potential, budget and the local revenue realization of disturbance permit levy. The potential of disturbance permit levy in 2009 collected from 3028 levy payers in 14 subdistricts amounted IDR 3,159,481,426